EFFECTIVENESS OF ANALGESIA WITH FENTANYL OR KETAMIN COMBINED MORPHINE OR MORPHIN ON ABDOMINAL SURGERY PATIENTS (Vietnam Journal of Community Medicine, 2022)
Objective: To compare the analgesic efficacy of fentanyl, morphine in combination with ketamineand morphine alone after abdominal surgery.Subjects and methods: Prospective clinical, randomized and controlled study on 90 patientsundergoing elective abdominal surgery at Vinh Long General Hospital from June 2021 to June 2022.Results: The analgesic effectiveness as lying still was similar between the three groups with theaverage VAS score at all time points below 3 points. The analgesic effectiveness as moving of thefentanyl group alone and the morphine-ketamine combination group were better than that of themorphine alone group at the time of evaluation on day 2. The percentage of patients with pain relieflevels from satisfied or above (all over 90%), A/D ratio (all > 74%) were similar between the threegroups.Conclusion: The analgesic effectiveness as lying still was similar between the three groups, whilethe analgesic effectiveness as moving was better in the fentanyl group and in the morphine-ketaminecombination group than in the morphine alone group (day 2).
Keywords: Abdominal surgery, fentanyl, morphine, ketamine.